The Interdisciplinary Role of Radiology, Laboratory Science, Internal Medicine, and Dentistry in Early Disease Detection and Management - Habib Fahed Khalaf Alshammari,; Faisal Ali Ghazai Alshammari,; Naif Kassab Mughyir Alshammari,; Zakaria Ali Almushaity,; Abdullah Ali Abdullah Al Khalifah,; Tareg Mohammad Alduaiji,; Mohammad Saleh Ali Aldaiji,; Mohammed Sulaiman Altukhaim,; Osama M. Alomari, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Early disease detection and management are important ways to improve patient outcomes and move toward precision medicine. Radiology, laboratory science, internal medicine, and dentistry will continue to be important contributors towards the achievement of this vision because each brings unique insight into the underlying biology and structural changes associated with disease. Such value propositions can be leveraged into higher rates of diagnostic accuracy, personalized treatments, and ultimately better patient care, provided that this is pursued in an environment of positive communication and collaboration among healthcare professionals. It is regrettable, however, that these values and resulting benefits are rarely realized due to a lack of uniform principles and practices, fragmentation in communication, and limited opportunities for interprofessional education and training. It will require success based on the implementation of integrated health records, interprofessional education, and investment in new technologies like artificial intelligence. Healthcare systems can realize new frontiers in early disease detection and management by capitalizing on the value brought by each discipline in a team-oriented approach to care, opening new avenues to provide more precise, personalized care that optimizes outcomes and maximizes population health.